StitchingPHm-A new algorithm for panoramic images - Silva, F. A.; Hiraga, A. K.; Artero, A. O. [UNESP]; Paiva, M. S.V. (My University, 2014)
In this paper it is presented a new algorithm for the construction of panoramic images (including 360 panoramas), which has as main characteristic to avoid the distortion that occurs by joining of several successive images in a sequence. We used the SIFT and RANSAC algorithms to find overlap areas between pairs of images, as well as a Blend algorithm for smoothing the joints. As the proposed algorithm doesn't cause distortions, the subsequent correction is not necessary, contributing to a better performance. The results of experiments using commercial software and also the proposed algorithm were compared through a visual analysis. In addition, a quantitative analysis was done using numeric measures calculated on a panoramic image, generated from an image sequence of a region mapped and georeferenced by Google Earth. © 2014 Pleiades Publishing, Ltd.
Keywords: 360 panorama; image adjustment; image rectification; RANSAC; SIFT